Metabolic insights into phosphofructokinase inhibition in bloodstream-form trypanosomes - Nare, Zandile; Moses, Tessa; Burgess, Karl; Schnaufer, Achim; Walkinshaw, Malcolm D.; Michels, Paul A. M. (Frontiers in Cellular and Infection Microbiology, 2023)
Previously, we reported the development of novel small molecules that are potent inhibitors of the glycolytic enzyme phosphofructokinase (PFK) of Trypanosoma brucei and related protists responsible for serious diseases in humans and domestic animals. Cultured bloodstream-form trypanosomes, which are fully reliant on glycolysis for their ATP production, are rapidly killed at submicromolar concentrations of these compounds, which have no effect on the activity of human PFKs and human cells. Single-day oral dosing cures stage 1 human trypanosomiasis in an animal model. Here we analyze changes in the metabolome of cultured trypanosomes during the first hour after addition of a selected PFK inhibitor, CTCB405. The ATP level of T. brucei drops quickly followed by a partial increase. Already within the first five minutes after dosing, an increase is observed in the amount of fructose 6-phosphate, the metabolite just upstream of the PFK reaction, while intracellular levels of the downstream glycolytic metabolites phosphoenolpyruvate and pyruvate show an increase and decrease, respectively. Intriguingly, a decrease in the level of O-acetylcarnitine and an increase in the amount of L-carnitine were observed. Likely explanations for these metabolomic changes are provided based on existing knowledge of the trypanosome’s compartmentalized metabolic network and kinetic properties of its enzymes. Other major changes in the metabolome concerned glycerophospholipids, however, there was no consistent pattern of increase or decrease upon treatment. CTCB405 treatment caused less prominent changes in the metabolome of bloodstream-form Trypanosoma congolense, a ruminant parasite. This agrees with the fact that it has a more elaborate glucose catabolic network with a considerably lower glucose consumption rate than bloodstream-form T. brucei.